HUBUNGAN ANTARA WARNING SIGN TERHADAP LAMA RAWAT INAP PASIEN INFEKSI DENGUE DI RSUD SUMEDANG TAHUN 2021 - Kamila Nursyahla, (2023)
Objective Dengue is a major health problem in tropical and subtropical regions, including Indonesia. Tens millions cases of dengue infection requiring hospitalization, up to 500 thousand people. WHO proposes seven warning signs that can identify the clinical severity. This study aims to determine the relationship between warning signs and length of stay of patients with dengue infection at Sumedang Hospital in 2021. Method This research was carried out in an observational analytic manner with a cross-sectional approach in patients with dengue infection. Samples were taken by simple random sampling method and bivariate data analysis using chi-square test and multivariate analysis using logistic regression test. Result The study was conducted on 96 patients collected from medical records. Patients were classified as prolonged (n=37) and non-prolonged (n=59) length of stay. Warning signs associated with length of stay were persistent vomiting (p=0.001, PR 2.592), mucosal bleeding (p=0.015, PR 2.169), and lethargy (p=0.000, PR 3.409). Conlusion The results of this study showed that the strongest factors of the warning sign that effected to the length of stay is mucosal bleeding and persistent vomiting.